The Factors Behind Bulgaria’s (Non) Convergence - Kirova, Silvia (European Journal of Economics and Business Studies, 2020)
This paper looks at the real convergence of Bulgaria in the period 1999-2018 and tries to identify and describe the factors that have stimulated or impeded the growth and the convergence of the economy. The research is based on the sigma-convergence method for estimation of the disparities in terms of real GDP per capita among the six Central and eastern European (CEE) countries with a derogation and among them and the average euro area income per capita. A comparative analysis is applied when analyzing the factors for convergence and their evolution in the period as Bulgaria is compared to the other CEE economies. The results of the research show the presence of a sigma convergence in the observed period. The convergence has been more pronounces in the first ten years. Although Bulgaria demonstrates one of the highest growth rates, this growth has not been sufficient to close the significant income gap between Bulgaria and the EU and euro area averages. While some factors have played positive role in the convergence process, some weaknesses have not been overcome and continue to play negative role and impede the convergence.
Keywords: real convergence, convergence factors, Bulgaria